2009
DOI: 10.1159/000247591
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell Death Postponed: Giving Apoptosis a Break?

Abstract: Glaucoma is characterised by the preferential death of retinal ganglion cells (RGCs). However, mammalian models indicate that neurons pass through a period in which they manifest signs of neuronal damage, but have yet to fully commit to death. Mounting evidence suggests that one of the clearest indications of this process is the reduction in RGC dendritic arborisation, resulting in functional compromise. The extent to which this may be reversible is unclear, since the molecular events that precede changes in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 342 publications
1
12
0
Order By: Relevance
“…There is compelling evidence that the expression of apoptotic factors is altered during neurodegenative diseases and ageing (McKernan et al, 2006;Kisiswa et al, 2009). In this study, we provide evidence that expression of IAPs is generally reduced during maturation of BN rat retina with a marked reduction in the expression of cIAP1.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There is compelling evidence that the expression of apoptotic factors is altered during neurodegenative diseases and ageing (McKernan et al, 2006;Kisiswa et al, 2009). In this study, we provide evidence that expression of IAPs is generally reduced during maturation of BN rat retina with a marked reduction in the expression of cIAP1.…”
Section: Discussionmentioning
confidence: 68%
“…The role of apoptosis in the elimination of RGCs in ageing and retinal pathology has been well documented (Spear, 1993;Quigley et al, 1995;Cecconi et al, 1998;Neufeld and Gachie, 2003). Recent work in the ageing and age related diseases such as glaucoma suggest that RGCs undergo a prolonged process of degeneration prior to elimination from the RGCL manifest as reduction in the complexity of the dendritic tree and the elimination of terminal processes (Watts et al, 2003;Whitmore et al, 2005;Williams et al, 2006;Kisiswa et al, 2009). These observations are consistent with those in other neuronal systems where parts of the neuron degenerate at different rates raising the possibility that during the early stages of degeneration, neuronal damage is associated with partial activation of programmed cell death (Whitmore et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of inhibitors of apoptosis were identified that exert their function by binding to pro-caspases to prevent their activation or to activated caspases to block their activity. 161 Excitotoxicity describes the process by which neurons are killed in response to excessive stimulation by neurotransmitters such as glutamate. This occurs when glutamate receptors such as the N-methyl-D-aspartate (NMDA) receptor and the a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor are over-activated by excess release of glutamate.…”
Section: Other Approachesmentioning
confidence: 99%
“…Consequently, reducing intraocular pressure is the primary therapeutic goal in the treatment of this condition. Recent studies have shown that the progression of glaucoma is associated with the apoptosis of ganglion cells (Quigley et al 1995;Kisiswa et al 2010). In the present study, we investigated the effect of one of the neuropeptides, pituitary adenylate cyclaseactivating polypeptide (PACAP), a pleiotropic neuropeptide that was originally isolated from ovine hypothalamic extract (Miyata et al 1989).…”
Section: Introductionmentioning
confidence: 99%